Decision Support System for Determining Tourist Attractions in Aceh Using the Android-Based Simple Multi-Attribute Rating Technique (SMART) - Mahdi; Muhammad Arhami; Nurul Azkiya (International Journal of Applied Artificial Intelligence and Robotics, 2025)
Choosing a tourist attraction often involves many complex factors that make it difficult for tourists to make tourist choices. Various aspects such as facilities, distance, transportation, entrance fees, parking spaces and road accessibility need to be evaluated systematically to facilitate decision making. This research develops an Android-based Decision Support System (DSS) using the Simple Multi-Attribute Rating Technique (SMART) method. The SMART method is used to assess tourist attractions based on six main criteria and several sub-criteria. The system development process includes planning, user interface design, implementation, and testing. Criterion weights are normalized to produce an objective final score. Functionality testing is carried out using the black-box method to ensure the reliability and effectiveness of the application. The application developed successfully underwent functionality testing with satisfactory results, achieving a pass percentage of 95.5%.